Les discussions à visée philosophique au prisme de la mixité - Bérengère Kolly (Nantes Université, 2016)
What the coeducation does to the philosophical discussions in school space? What the philosophical discussions can do to the coeducation? The philosophical discussions are a place of neutral reflexivity, so a place to prove of the identity of the two sexes in the thought. This article presents a short study about discussions conducted in a secondary school. It shows that the friends and peers - who frequently are of the same sex - possess a considerable part in the inertia or the change, towards equality between the sexes, in education.